I'm a CANCER BIOLOGIST now! - Park, Ben Ho (Singapore : WS Education, 2023)
What is a cancer biologist? What does he or she do? Meet Ben, a kid like you and me, who grew up and became a cancer biologist. As a child, Ben loved playing basketball and reading books, especially Spiderman comic books. In middle school, he fell in love with science and understanding the human body. Learn about how he uses a special technique, called a liquid biopsy, to detect the mutations that cause cancer and about how liquid biopsies help people with cancer know if they are cured.The Who Me? series features inspirational biographies of scientists who young readers will be able to identify with as people like themselves. Written by the scientists themselves and co-authors from Vanderbilt University, the books are designed to help young readers understand that scientists are regular people like themselves who are excited about learning and discovering new things and who decided to work hard in school in order to create for themselves the opportunity to become scientists. As they learn the stories of these scientists, readers will also learn some basic science ideas, that are well-explained and easily understood, and be introduced to the cutting-edge science these scientists are working on today.
Keywords: Park, Ben Ho, -- Juvenile literature; Cancer -- Research -- Juvenile literature; Biologists -- Biography -- Juvenile literature; Autobiographies